Implementasi Profile Matching pada Sistem Pendukung Keputusan Seleksi Peserta Tenda Kewirausahaan - Setiawan, Aries; Nuryanto, Imam; Mintorini, Ery; Hidajat, Moch. Sjamsul; Farida, Ida; Widjajanto, Budi; Prasetya, Jaka; Lewa, Andi Hallang; Karmila, Karmila (Universitas Wahid Hasyim, 2024)
One of the programs from the Entrepreneurship Unit is the entrepreneurial tent participant program. In the manual assessment process, participant selection is only based on the type of entrepreneurial product that will be offered. However, this does not get maximum selection results because if the existing selection only uses one variable component and the assessment tends to contain elements that have no potential. One decision making method that has weight in its calculations is profile matching. Profile matching works by assigning a standard value to each variable and a weighted value is also assigned to the variable. Next, look for differences in participant scores and standard scores for each variable. The ranking results resulting from profile matching are a combination of several variables with different weight levels. Therefore, in assessing the selection of entrepreneurial tent participants, it is best to use the existing calculation pattern using the profile matching method. The weight of each variable is determined by the decision maker, in this case the head of Entrepreneurship. With different percentage weight values ​​for each variable, it will provide assessment results that are in accordance with the level of competency of the entrepreneurial tent selection participants.